The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.18195/issn.0312-3162.22(3).2004.241-251
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the family Littorinidae (Mollusca: Gastropoda) in Thailand

Abstract: The distribution of the family Littorinidae in mangroves and on rocky shores in Thailand was studied, Fourteen species of Lilloraria, Eehino!lltorina and Peaslella were recorded from 50 survey sites, bringing the total known for the country to 16 species. Two species were recorded for the first time in Thailand Ul10rarza eO/liea was found in only two places in southern Thailand, both on the Andaman Sea, Eehinolitlorina feejeensis occurred on scattered granite rocks on sandy beaches in the splash zone of offsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…As reported by the Sanpanich et al [26] and Suresh et al [27], Littoraria undulata only occurred in the rocky outcrop with mangrove environment. Ramadoss [28], Tan and Clements [29], Arumugam et al [8], Haragi et al [20], Khade and Mane [19], Sorensen [30], Miloslavich et al [31] and David [6] was reported rocky outcrop species were also present in this study area also in the same environment.…”
Section: Discussionsupporting
confidence: 52%
“…As reported by the Sanpanich et al [26] and Suresh et al [27], Littoraria undulata only occurred in the rocky outcrop with mangrove environment. Ramadoss [28], Tan and Clements [29], Arumugam et al [8], Haragi et al [20], Khade and Mane [19], Sorensen [30], Miloslavich et al [31] and David [6] was reported rocky outcrop species were also present in this study area also in the same environment.…”
Section: Discussionsupporting
confidence: 52%
“…Lastly, this study adds to the database on the distribution of marine gastropods of the country along the east coast of the Gulf of Thailand. Collection ,A [18], [19], [20] Tectus niloticus (Linnaeus, 1767) 20,37,40,51, [21],W [17],A [18], [19], [20] Trochus radiatus Gmelin, 1791 A [18], [19], [20] Umbonium vestiarium (Linnaeus,1758) 14,15,17,24-27,30,51, [21], A [18], [19], [20] Family Angariidae Littoraria carinifera (Menke, 1830) 1,32, [22],A [20] Littoraria conica(Philippi, 1846) A [22] Littoraria intermedia (Philippi, 1846) [22] Littoraria melanostoma (Gray,1839) 1,32, [21], [22] Littoraria pallescens (Philippi, 1846) 1,32,41, [21], [22] Littoraria scabra(Linnaeus,1758) A [18], [19], [20], [22] Littoraria strigata (Philippi, 1846) 1,32, A [18], [19], [20], [22] Littoraria undulata (Gray, 1839) A [20], [22] Peasiella roepstorffi ana (Nevill, 1885 Polinices mammilla (Linnaeus, 1758) 2 -9 , 11 -1 5 , 1 7 -2 0 , 2 5 -2 9 , 3 8 , 3 9 , 4 1 , 4 2 , 4 4 , 4 6 -5 5 , [21],W [17],A [18], [19], [20] Polinices powisianus (Récluz, 1844) 10,38…”
Section: Discussionmentioning
confidence: 99%
“…List of gastropods collected at sites along the east coast of the Gulf of Thailand. A = record in Andaman Sea; W = record in west of the Gulf of Thailand; Duangdee et al[17]; Department of Marine Science[18]; Forestry Research Center[19]; Duangdee et al[20]; Duangdee[21]; Sanpanich et al[22] …”
mentioning
confidence: 99%
“…Furthermore, littorinids are highly mobile, migrating vertically downwards to feed at lower levels on the trees or to spawn, and upwards to avoid submersion by the rising tide (Reid, 1984;Yipp, 1985;Kohlmeyer & Bebout, 1986;Ohgaki, 1992;Lee & Williams, 2002b). Horizontal migration between trees is, however, very limited, because most snails are unable to crawl on the mud surface (Reid, 1985; but see Sanpanich et al, 2004), so that horizontal distribution cannot be ascribed to adult behaviour patterns. The present study quantifies differences in abundance between three horizontal strata: seaward, middle and landward, but did not examine vertical distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Macnae, 1968; but see Ellison, 2002), associations between tree and littorinid species could determine distribution of the snails. However, although differences in occurrence of Littoraria species on mangrove genera have been observed, these appear to be mainly the incidental consequences of tree architecture combined with a substrate preference for bark or leaves, and no obligate or dietary associations have been recorded (Reid, 1985(Reid, , 1986Ohgaki, 1992;Boneka, 1994;Lee & Williams, 2002a;Sanpanich et al, 2004). Littoraria species are generalist feeders on plant material, epiphytic microalgae and fungal hyphae, but (with the exception of leaf hairs of Avicennia) rarely ingest living leaf cells (Kohlmeyer & Bebout, 1986;Reid, 1986;Bärlocher & Newell, 1994;Lee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%